Justice for all? Access by ethnic groups to the English royal courts in Ireland, 1252-1318 - HEWER, STEPHEN (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2018)
The notion that all Gaelic people were immediately and ipso facto denied access to the royal courts in Ireland, upon the advent of the English in c.1169, has become so established in the national consciousness of Ireland that it is no longer questioned. This thesis questions this narrative of absolute ethnic discrimination in thirteenth- and early fourteenth-century English Ireland on the basis of a thorough re-examination of the Irish plea rolls. These records exist primarily in the form of nineteenth-century transcripts, the originals having been destroyed in the explosion in 1922. A forensic study of these records reveals a great deal of variation in how members of various ethnic groups who came before the royal courts in Ireland were treated. Specifically, the thesis demonstrates the existence of a large, and hitherto scarcely noticed, population of Gaels with regular and unimpeded access to English law, identifiable as Gaelic either through explicit ethnic labelling in the records or implicitly through their naming practices. This represents a primary contribution of the research. To achieve a fuller understanding of the legal status of Gaels within English Ireland, the thesis compares their treatment to that of the English of Ireland and it also offers an in-depth examination of other ?Irish Sea Region? ethnicities. While the Englishmen are only included for reasons of comparison, the legal treatment of women, Ost-people, Welsh, Manx, Islanders, and Scots reveals that English Ireland was not a simple dichotomy between the English and the unfree. Having established the legal status of these various groups in civil proceedings, the thesis proceeds to examine their treatment in criminal cases. The rules of law allowed for different treatment of peoples in criminal trials and civil proceedings. This was not limited to the fact that defendants could be hanged, but also it allowed seemingly-unfree people (and people of ?liminal? status) to enter court and indictments prosecuted crimes against the unfree. The thesis also offers an analysis of Gaelic (and other) clerics. Religious men and women are treated separately because the royal courts did likewise. Prelates, especially, received extraordinary privileges in civil and criminal cases. The English administration in Ireland permitted certain religious men to exact harsher labour services from their tenants (when compared to secular lords). The courts also acquiesced to prelates manipulating the legal system to disseise free Gaels. These last two factors are important for contextualising the actions of certain Gaelic prelates, which have been framed as benevolent and altruistic. The primary results of the thesis are that Gaelic men and women were free members of English Ireland, the society was cosmopolitan, the law was a system of remediation and not codified, and that despite increasing hostilities the people of English Ireland were never a dichotomy. Complexity defined the land.
APPROVED
Keywords: Medieval; Law; Society; Ireland; Ethnicity; Sex; Gender; Gaels; Gaelic; Ost-people; Identity